Analysis of the fusion performance, beam–target neutrons and synergistic effects of JET's high-performance pulses. (12th March 2021) - Kirov, K.K.; Belonohy, E.; Challis, C.D.; Eriksson, J.; Frigione, D.; Garzotti, L.; Giacomelli, L.; Hobirk, J.; Kappatou, A.; Keeling, D.; King, D.; Lerche, E.; et al.
Abstract: Achieving high neutron yields in today's fusion research relies on high-power auxiliary heating in order to attain required core temperatures. This is usually achieved by means of high neutral beam (NB) and radio frequency (RF) power. Application of NB power is accompanied by production of fast beam ions and associated beam–target (BT) reactions. In standard JET operational conditions, deuterium (D) NBs are injected into D plasmas. The injected beams comprise D atoms at full, one-half and one-third injected energy. Typically, the full energy of the injected D beams is between 90 and 120 keV, providing 1.4–2.0 MW of heating, which is about half of the injected power. Half-energy D beams carry about one-third of the injected power and the rest of the power is carried by the third energy fraction of D beams. Under these conditions, thermal fusion reactions, i.e. those between plasma ions, and BT reactions are of the same order of magnitude. This study addresses important issues regarding the impact of density, central electron and ion temperatures and their ratio, T i (0)/ T e (0), on fusion performance, measured by the total neutron yield and BT neutron counts. NB/RF synergistic effects are discussed as well. It is demonstrated that thermal fusion gain increases linearly with normalised plasma pressure, β N, and confinement, B t τ . The BT neutrons are, however, more difficult to predict and this task in general requires numerical treatment. In this study, BT neutrons in JET's best-performing baseline and hybrid pulses are analysed and the underlying dependencies discussed. Central fast ion densities are found to decrease with increased density and density peaking. This is attributed to poorer beam penetration at high density. The BT reactions however are unchanged and can even increase if operating at higher core temperatures. An increase in the central ion temperature and T i (0)/ T e (0) ratio leads to higher total and BT reaction rates whilst simultaneously the ratio of the BT to total neutron decreases significantly. NB/RF synergistic effects are found to have a negligible impact on total neutron rate. This can be explained by the reduced beam penetration in high-density conditions leading to lower central fast ion density.